Atlas of Mediastinal Pathology - Suster, Saul (Atlas of Anatomic Pathology, 2015)
The mediastinum is a virtual compartment in the chest cavity that is the seat of several vital organs and structures that can be involved in a variety of pathologic processes, including congenital and developmental abnormalities, inflammatory conditions, and benign and malignant neoplasms. The Atlas of Mediastinal Pathology provides a pictorial survey of the major disease processes that can affect this anatomic compartment, including congenital and acquired cysts, benign hamartomatous processes, inflammatory processes involving the mediastinum, and benign and malignant neoplasms. The latter includes tumors of the thymus (thymoma and thymic carcinoma), neuroendocrine neoplasms, germ cell tumors, mesenchymal neoplasms, and hematolymphoid malignancies. The use of ancillary diagnostic methods is illustrated, where appropriate, providing assistance for pathologists in arriving at the correct diagnosis.